2001
DOI: 10.1029/2001jd900018
|View full text |Cite
|
Sign up to set email alerts
|

Particle formation and growth from ozonolysis of α‐pinene

Abstract: While only one component was required to simulate the data, more than one product may have been involved, in which case the one component must be viewed as a surrogate having an effective SVP of 0.01 ppb or less. Adding trace amounts of SO2 greatly increased the nucleation rate while having negligible effect on the overall aerosol yield. We are unable to explain the observed nucleation in the a-pinene/ozone system in terms of classical nucleation theory. The nucleation rate and, more importantly, the slope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
9
42
0
Order By: Relevance
“…The decrease in the SO 2 concentration leads to a reduced sulfate formation (see http://www.nilu.no/ projects/ccc/emepdata.html), which is also detected at the Jungfraujoch with a yearly trend of À3.3% yr À1 and monthly trends between 6 and 12% yr À1 during the October to January period (Tables 1 and 2). Smog chamber experiments on ozonolysis of a-pinene showed that addition of trace amounts of SO 2 greatly enhanced the nucleation rate [Hoppel et al, 2001]. One possible explanation is that reduced SO 2 leads to lower nucleation rates and in turn preferential condensation on the preexisting aerosol and therefore a greater mean aerosol size of the accumulation mode particles also for the ambient aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the SO 2 concentration leads to a reduced sulfate formation (see http://www.nilu.no/ projects/ccc/emepdata.html), which is also detected at the Jungfraujoch with a yearly trend of À3.3% yr À1 and monthly trends between 6 and 12% yr À1 during the October to January period (Tables 1 and 2). Smog chamber experiments on ozonolysis of a-pinene showed that addition of trace amounts of SO 2 greatly enhanced the nucleation rate [Hoppel et al, 2001]. One possible explanation is that reduced SO 2 leads to lower nucleation rates and in turn preferential condensation on the preexisting aerosol and therefore a greater mean aerosol size of the accumulation mode particles also for the ambient aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were conducted in Calspan's 590 m 3 environmental chamber during October and November 1998; Details of the chamber and its instrumentation, along with results from selected case studies on the ozonolysis of α-pinene are given by Hoppel et al (2001). To illustrate the use of PARGAN, we apply it to an experiment in which SO 2 oxidation resulted in particle nucleation and growth.…”
Section: Application To Smog Chamber Measurements: Wall Loss Coagulamentioning
confidence: 99%
“…For small particles, wall loss by diffusion is most important, while for larger particles, loss by gravitational settling is larger. A number of chamber studies (Crump and Seinfeld, 1981;McMurry and Rader, 1985;Bienenstock, 2000;Hoppel et al, 2001) have reported a first order rate constant, k diff (r), for diffusional wall loss that is proportional to the square root of the Brownian diffusion coefficient, D B (r). Thus, k diff (r) is given by…”
Section: First Order Loss Processesmentioning
confidence: 99%
“…In boreal forests, α-pinene is the most abundant monoterpene. It has been extensively studied in laboratory experiments during the past decades due to its large SOA formation potential (Hoppel et al, 2001; Lee and Kamens, 2005;Eddingsaas et al, 2012a). Several oxidation pathways are known (see Fig.…”
Section: A P Praplan Et Al: Elemental Composition and Clustering Bmentioning
confidence: 99%